Role of salt tablets in the treatment of perioperative hypotension in patients with pheochromocytoma - Jesus Andres Montano Saavedra, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Pheochromocytomas (PHEOs) and paragangliomas (PGLs) are rare and clinically important chromaffin cell tumors that typically arise, respectively, from the adrenal gland and from extra-adrenal paraganglia. Neuroendocrine tumors which have the potential to secrete catecholamines are either associated with sympathetic adrenal (pheochromocytoma) or nonadrenal (paraganglioma) tissue. Surgical removal of these tumors is always indicated to cure and prevent cardiovascular and other organ system complications associated with catecholamine excess.The clinical features and consequences of PHEO/PGL result from the release of catecholamines (norepinephrine and epinephrine). An undetected PHEO/PGL poses a hazard to patients undergoing surgery, childbirth, or general anesthesia, because of the potential for excess catecholamine secretion, which can result in significant, often catastrophic outcomes.Pheochromocytomas can be divided into two main categories: EPI secreting PPGLs that cause decreased cardiac contractility owing to downregulation of β-adrenoceptors and NE secreting PPGLs causing a decrease in circulating plasma volume secondary to α1-adrenoceptor mediated vasoconstriction leading to postural hypotension. Diagnosing and localizing a PHEO/PGL can be challenging. Plasma and urinary catecholamines as well as their metabolites and radio-iodinated metaiodobenzylguanidine (MIBG) scanning can yield false-positive/negative results in patients harboring the tumor, and computed tomography (CT) and magnetic resonance imaging (MRI) lack sufficient specificity. The molecular mechanisms by which genotypic changes predispose to the development of PHEO/PGL remain unknown, even in patients with identified mutations.